Refugees from Central American gangs - Kennedy, E (Refugee Studies Centre, University of Oxford, 2013)
El Salvador, Guatemala and Honduras are among the world’s most fragile nations, yet they are largely ignored by refugee agencies who underestimate transnational criminal organisations’ abuses and powers of control, while overestimating national governments’ ability and willingness to protect their citizens.